Implementasi Sistem Otomasi Takaran Biji Kopi Pada Tempat Penyimpanan di Mesin Penggiling Kopi - Fachrur Febriansyah Manangkalangi; Rizal Maulana; Gembong Edhi Setyawan (Fakultas Ilmu Komputer (FILKOM), Universitas Brawijaya, 2020)
Entrepreneurs who have established small coffeeshop business for a long time, using coffee grinder machine which has no automatic scale tchnology inside, absolutely wish that kind of technology exist in their machines without replacing with the new ones. From that problem statement, the researcher will provide solution by creating coffee beans automatic measuring system in the storage of the grinder which there is not any automatic scale technology. This system will use load cell censor hardware with HX711 module as an object reader, in this case is coffee beans in the hopper. This system will also use stepper nema 17 motor whose end has already connected with artificial component in the form of auger and driver A4988 which is used as actuator to the coffee beans in the hopper. There is also 16x2 LCD with 12C module used as whole information display of the process, from the beginning until the end. It has three push buttons utilized by users to choose three mass measuring target of the system and it use servo motor as a open-close valve between the prototype tool and grinding machine. Then, the analysis result for this system testing can be concluded that there is 16,9% error to the digital scale tool, whereas for monitoring analysis, the whole information dislpayed on LCD monitor gain good system testing result in displaying all the system information. The next analysis is motor stepper actuator to the coffee beans capacity in the hopper and the result of motor stepper movement is 100%. It means that the movement towards the coffee beans capacity in the hopper is good. It moves very well. The conclusion of the final testing analysis to the entire system is the researcher gain 100% for accuracy of the entire system and it can be stated that it can work properly just as the purpose of this research.